Hydrothermal Synthesis of Urchin‐like Bi2S3 Nanostructures for Superior Visible‐light‐driven Cr(VI) Removal Capacity. Issue 25 (3rd July 2018) - Sang, Yan; Dai, Guangdong; Wang, Lvxuan; Gao, Xueyou; Fang, Caihong
Abstract: In this work, large amounts of urchin‐like Bi2 S3 nanostructures assembled from radially oriented nanorods were prepared by a simple hydrothermal method. The as‐prepared Bi2 S3 nanostructures possess an orthorhombic crystal structure with a high crystallinity. More importantly, the obtained Bi2 S3 nanostructures are spherical architectures composed of large quantities of nanorods with highly active sites. This attractive architecture can provide a large active surface area for photocatalysis. The photodegradation of Cr(VI) under visible light irradiation indicated that 95% of Cr(VI) was degradated within 30 min using the as‐prepared Bi2 S3 nanoparticle as a photocatalyst. Further investigations revealed that the pH value of the solution has a significant effect on the photocatalytic reduction ability as well. Significantly, the kinetic constant of urchin‐like Bi2 S3 nanostructures for Cr(VI) degradation is about 100 times that of Bi2 S3 nanoflowers and commercial P25. Furthermore, the photocurrent of urchin‐like Bi2 S3 nanostructures is still higher than that of Bi2 S3 nanoflowers. We believed that the urchin‐like Bi2 S3 nanostructures are promising materials for Cr(VI) photoreduction. Abstract : Urchin‐like Bi2 S3 nanostructures assembled from radially oriented nanorods by a facile solvothermal approach without any template and surfactant. This attractive architecture can provide a large active surface area for photocatalysis. Significantly, the obtained Bi2 S3 catalyst displayed a high performance for the photocatalytic reduction of Cr(VI). And the kinetic constant of urchin‐like Bi2 S3 nanostructures for Cr(VI) degradation is about 100 times that of Bi2 S3 nanoflowers and commercial P25.